Pengaruh Customer Value Terhadap Kinerja Customer Relationship Management (Studi Pada Perilaku Pelanggan Starbucks Di Kota Bandar Lampung) - Rabindra, Rabindra; Narundana, Vonny Tiara (Jurnal Mirai Management, 2024)
Introduction/Main Objectives: This study aims to explore the influence of customer value on the quality of customer relationship management at Starbucks, focusing on the city of Bandar Lampung, to understand the relationship and behavior of customers with the brand. The research method employed is simple regression with a 100 samples, where questionnaires are distributed to Starbucks Card owners who have topped up their balances at least twice at Starbucks outlets in Bandar Lampung. Data collection is done through questionnaires distributed to Starbucks Card owners in Bandar Lampung, with analysis conducted using SPSS software with regression analysis. The findings indicate that Customer Value has a positive impact on CRM at Starbucks in Bandar Lampung. This means that the more effectively Starbucks manages customer values, the better the company will be at maintaining and strengthening relationships with customers, with the expectation that customers will become increasingly loyal in purchasing Starbucks products. Keywords: Customer, CRM, Starbucks